Detecting acute kidney injury in horses by measuring the concentration of symmetric dimethylarginine in serum - Siwinska, Natalia (Acta Vet Scand, 2021)
BACKGROUND: Acute kidney injury (AKI) in horses may develop as a complication of a primary disease or following the administration of nephrotoxic drugs, and may pose a diagnostic challenge. Hence, the main objective of this study was to evaluate the concentrations and diagnostic significance of serum symmetric dimethylarginine (SDMA) and conventional renal dysfunction biomarkers in healthy horses, horses at risk of developing AKI, and horses with clinically evident AKI. A second aim was to assess how gastrointestinal disease and exposure to potentially nephrotoxic drugs affected SDMA levels. Thirty healthy horses, 30 horses with gastrointestinal disease and/or receiving phenylbutazone or gentamicin (risk group) and 11 horses with AKI were included in the study. Serum SDMA levels were measured using commercially available enzyme immunoassay tests. RESULTS: SDMA levels in healthy horses, horses at risk of AKI and horses with AKI were 12 µg/dL (11–14), 12 µg/dL (11–13) and 20 µg/dL (20–37), respectively (all results presented as a median (quartile 1–quartile 3)). There was a significant difference in SDMA concentration between the healthy horses and those with AKI, whereas the SDMA levels in healthy horses and those at risk of AKI were comparable. A SDMA cut-off value of 19 µg/dL was established. Horses from the risk group had higher urine protein concentration and urine protein to creatinine ratio compared with healthy horses. Furthermore, horses with colic from the risk group presented with elevated urine γ-glutamyl transpeptidase to creatinine ratio. CONCLUSION: The SDMA cut-off value established in healthy horses was higher than previously reported. The SDMA level correlated with the azotaemia levels. Horses from the AKI risk group had normal SDMA levels but single urine parameters was abnormal indicating their higher sensitivity in assessing subclinical kidney dysfunction.